The city school number workbook nursery (Albakio International,The City school Lahore, 2012)
This workbook is designed for nursery-level students at The City School, focusing on enhancing their numerical understanding and foundational math skills during Term 2. It aims to engage young learners through interactive activities that promote counting, number recognition, and simple arithmetic operations. Each section incorporates vibrant illustrations and hands-on exercises to make learning enjoyable and effective. By fostering a positive attitude towards mathematics, the workbook prepares students for more advanced concepts in future terms, ensuring a solid grounding in essential numerical competencies.